The Difficulty of Leaving: Freedom of Movement and the National Security State in Cold War West Germany. Issue 1 (February 2023) - Gehrig, Sebastian
Histories of the freedom of movement during the Cold War often focus on issues of immigration. Yet, national security frameworks set up after the Second World War also involved restrictions of the right to leave one's own country. This article takes the Federal Republic of Germany as a case study to probe the political tensions between codified constitutional rights of the individual, new human rights norms, and the Bonn government's anti-communist mobilisation during the 1950's. The example of the right to leave shows that the state retained crucial powers to curtail basic rights in the name of national security state.